Evaluation of conditions of life of inhabitants in the Middle East Region with focus on Bahrain - A.Rasool, Mahmood Husain Mohamed (Univerzita Pardubice, 2017)
The aim of the thesis to is to evaluate conditions life of inhabitants and contribute for having a better view about living conditions in the Middle East (Arabian Peninsula) and explain the concept of quality of life and their measure. An attention is paid to the situation in Bahrain.
Hodnocení životních podmínek v regionu Středního východu se zaměřením na Bahrajn
Keywords: Quality of life; Middle East; Bahrain; standard of living; Human development index; Arabian Peninsula; Kvalita života; Střední východ; Bahrajn; životní úroveň; Index lidského rozvoje; Arabský poloostrov